The Effect of Relaxation and Slow Breathing Technique (RSBT) as A Non-Pharmacological Intervention on Blood Pressure Level Among Stage 1 Hypertensive Older Adults - Arif Rakhman; Khodijah (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2023)
The prevalence of hypertension is relatively high, and the number still increases by year. Various studies have demonstrated that non-pharmacological methods have been shown capable of lowering blood pressure such as relaxation techniques, and also slow breathing technique. This study aims to determine the effects of relaxation and slow breathing technique (RSBT) on blood pressure level among stage 1 hypertensive older adults. This study utilized quantitative research method and the research design employed in this study is the one group interrupted time series pre-test post-test quasi-experimental design. Two types of instruments were used in this study to gather the pertinent data and information. The researcher utilized the checklist form to record the result of observation. The researcher also utilized biophysiologic instrument to measure to measure the blood pressure level of the participants. The participants of the study were ten (10) male and ten (10) female older adults with stage 1 hypertension who were selected through purposive sampling technique. Repeated-Measures ANOVA and the Post Hoc test was utilizing series of t-test. The result shows that there is a significant difference in the systolic and diastolic blood pressure level among participants before and after the implementation of the RSBT in both initial phase (first week) and reinstituted phase (third week). Prolonging of implementation of RBST would be more powerful to reduce blood pressure level among older adult with stage I hypertension